Mice Deficient in AKAP13 (BRX) Are Osteoporotic and Have Impaired Osteogenesis. (10th May 2015) - Koide, Hisashi; Holmbeck, Kenn; Lui, Julian C; Guo, Xiaoxiao C; Driggers, Paul; Chu, Tiffany; Tatsuno, Ichiro; Quaglieri, Caroline; Kino, Tomoshige; Baron, Jeffrey; Young, Marian F; Robey, Pamela G; et al.
Abstract: Mechanical stimulation is crucial to bone growth and triggers osteogenic differentiation through a process involving Rho and protein kinase A. We previously cloned a gene ( AKAP13, aka BRX ) encoding a protein kinase A‐anchoring protein in the N‐terminus, a guanine nucleotide‐exchange factor for RhoA in the mid‐section, coupled to a carboxyl region that binds to estrogen and glucocorticoid nuclear receptors. Because of the critical role of Rho, estrogen, and glucocorticoids in bone remodeling, we examined the multifunctional role of Akap13. Akap13 was expressed in bone, and mice haploinsufficient for Akap13 ( Akap13 +/– ) displayed reduced bone mineral density, reduced bone volume/total volume, and trabecular number, and increased trabecular spacing; resembling the changes observed in osteoporotic bone. Consistent with the osteoporotic phenotype, Colony forming unit‐fibroblast numbers were diminished in Akap13 +/– mice, as were osteoblast numbers and extracellular matrix production when compared to control littermates. Transcripts of Runx2, an essential transcription factor for the osteogenic lineage, and alkaline phosphatase ( Alp ), an indicator of osteogenic commitment, were both reduced in femora of Akap13 +/– mice. Knockdown of Akap13 reduced levels of Runx2 and Alp transcripts in immortalized bone marrow stem cells. These findings suggest that Akap13 haploinsufficient mice have a deficiency in early osteogenesis with a corresponding reduction in osteoblast number, but no impairment of mature osteoblast activity. © 2015 American Society for Bone and Mineral Research.